Peningkatan Kompetensi Guru Informatika SMA Melalui Program Edukasi Koding dan Kecerdasan Artifisial di Kabupaten Indramayu - Muhamad Mustamiin; Alifia Puspaningrum; Didin Wahyudin (Madani : Indonesian Journal of Civil Society, 2026)
The integration of the Koding and Kecerdasan Artifisial (KA) curriculum as an elective subject by Kemendikdasmen starting in the 2025/2026 academic year urgently requires an improvement in the competence of SMA Informatika teachers in Kabupaten Indramayu in implementing the curriculum. Based on data collection and interview results, it was found that some teachers have not used coding as a main learning topic for quite some time and are relatively unfamiliar with kecerdasan artifisial, so this will positively correlate with the quality of learning. Therefore, this program aims to address this gap through a series of structured activities, including coding material training using the Python language, coding learning exercises via an online judge application, presentation of kecerdasan artifisial material, and coding implementation on a product prototype. The implementation of the program utilized the facilities available at Politeknik Negeri Indramayu as the training venue. The training results showed that all participants felt satisfied with the implementation of the training activities, and the participants' understanding scores regarding coding increased, with an average post-test score of 86.48%. This is expected to be a positive signal capable of strengthening the quality of teachers in Kabupaten Indramayu, particularly in the field of Informatics.